PENDIDIKAN AKHLAK ANAK KEPADA ORANG TUA DALAM PERSPEKTIF AL-QURAN - Murharyana Murharyana; Ibnu Imam Al Ayyubi; Rifqi Rohmatulloh (Piwulang: Jurnal Pendidikan Agama Islam, 2023)
The Al-Quran is a guide for human life from various fields and settings of life that every human being passes through, including teaching about doing good to both parents. One of the verses related to doing good to both parents is Al-Quran Surah al-Ahqof verses 17-20. It explains the prohibition and notification of the condition of a person who is miserable as a result of disobedience to both parents, especially disobedience to a mother because a mother's rank is higher than that of a father, and how a child must obey and respect the position of parents under any circumstances and in position they must look after and take care of parents. Both parents always pray for their child to become a pious child and ask Allah SWT for help to avoid punishment. The method used in this study uses a descriptive qualitative method with a bibliography/reference study of the interpretation of the Koran relating to the verses of doing good to parents. The purpose of this writing or research is to open insight for parents and children on how to play an active role in building noble character.